2014
DOI: 10.1002/j.2168-0159.2014.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

3.1: Invited Paper: Oxide Versus LTPS TFTs for Active‐Matrix Displays

Abstract: We have reviewed the comparison of LTPS and Oxide TFTs for AMOLED backplane application. The device performance and stability of ELA based LTPS TFTs are excellent even though the process cost is much higher than that of oxide TFTs. Oxide TFTs, on the other hand, can be manufactured with lost cost and the device performance is good enough for large-area AMOLED backplane. However, run-to-run reproducibility and bias stability of oxide TFTs are much inferior to those of their LTPS counterparts. We propose the bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Hence, there are only a few mass production factories of large panel. In contrast, a lot of studies have reported about improving photo‐stability, such as c‐axis‐aligned crystal‐indium gallium zinc oxide and dual gate …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence, there are only a few mass production factories of large panel. In contrast, a lot of studies have reported about improving photo‐stability, such as c‐axis‐aligned crystal‐indium gallium zinc oxide and dual gate …”
Section: Introductionmentioning
confidence: 98%
“…In contrast, a lot of studies have reported about improving photo-stability, such as c-axis-aligned crystal-indium gallium zinc oxide 7-9 and dual gate. 10 In light of these issues, we developed PLAS for novel laser annealing technology, which had the mobility of 28.1 cm 2 /Vs larger than that of mass produced oxide TFT and photo-stability comparable with that of LTPS TFT in bottom gate structure. This innovative technology enables the conversion from an α-Si TFT to a high-mobility TFT most easily and inexpensively.…”
Section: Introductionmentioning
confidence: 99%
“…Low temperature poly silicon (LTPS) technology and amorphous type TFT is the two mainstream backplane for LCD driving. Recent years, the IGZO TFT backplane technology had been developed very rapidly [1]. Compare with amorphous type, LTPS well known has high mobility, anti-stress ability and smaller size layout space [2].…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous-indium-gallium-zinc-oxide (a-IGZO) thin-film transistors (TFTs) have been considered as good candidate for active-matrix organic light-emitting diode (AMOLED) pixel circuit since they can be made using a relatively simple process and have high mobility and transparent characteristics [1][2][3]. However, because their reliability still has some problems, the compensated pixel circuit is mandatory for AMOLED panel [4][5][6].…”
Section: Introductionmentioning
confidence: 99%